Graduate Medical Education. (September 2015) - Aschenbrener, Carol A.; Ast, Cori; Kirch, Darrell G.
<x xml:space="preserve">Abstract</x> Nearly half a century ago, Lowell T. Coggeshall recommended, through what has come to be known as the Coggeshall Report, that physician education—medical school (or undergraduate medical education [UME]), residency training (or graduate medical education [GME]), and continuing medical education (CME)—be "planned and provided as a continuum." While the dream of a true continuum remains unfulfilled, recent innovations focused on defining and assessing meaningful outcomes at last offer the anchor for the creation of a seamless, flexible, and ongoing pathway for the preparation of physicians. Recent innovations, including a widely accepted competency framework and entrustable professional activities (EPAs), provide key tools for creating a continuum. The competency framework is being leveraged in UME, GME, and CME and is serving as the foundation for the continuum. Learners and those who assess them are increasingly relying on observable behaviors (e.g., EPAs) to determine progress. The GME community in the United States and Canada has played—and continues to play—a leading role in the creation of these tools and a true medical education continuum. Despite some systemic challenges to implementation (e.g., premedical learner formation, time-in-step requirements), the GME community is already operationalizing these tools as a basis for other innovations that are improving transitions across the continuum (e.g., competency-based progression of residents). The medical education community's greatest responsibility in the years ahead will be to build on these efforts in GME—joining together to learn from one another and develop a continuum that serves the public and the profession.